Effect of Coupling Agent on Mechanical and Physical Properties of Non-Woven Kenaf Fibre Mat Reinforced Polypropylene Composites - et al., R.A.E. Roslan (International Journal of Advanced Science and Technology, 2019)
Non-woven kenaf fibre mat (NWKFM) reinforced polypropylene (PP) biocomposite have been prepared using sandwich structure and hot press moulding technique. However, natural fibres and polymer is chemically incompatibility. So, in order to enhance the interfacial bonding between the kenaf fibre and PP, NWKFM was chemically treated using 1%, 3%, 5% and 7% of maleic anhydride grafted polypropylene (MAPP). Fourier transform infrared (FTIR) was used to determine the chemical structural and functional groups in both treated and untreated NWKF. The mechanical and physical testing for both untreated and treated non-woven kenaf fibre mat filled PP (NWKFPP) composites were conducted. Overall, the result shows that, 3% MAPP-treated NWKFPP demonstrated the optimum performance in mechanical and water absorption properties compared to others amount of MAPP. Thus, the addition of MAPP as coupling agent in NWKFPP enhances the fibre-matrix adhesion, which is also contributed to the increasing of mechanical and physical properties of NWKFP.